2023
DOI: 10.1039/d2nj06206b
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation and optimization of a CsPbI3-based perovskite solar cell to enhance the power conversion efficiency

Abstract: In this study, we investigated the potential of CsPbI3 as an absorber material for use in perovskite solar cells (PSCs). To optimize the device, we used TiO2 as the electron...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 127 publications
(54 citation statements)
references
References 86 publications
4
50
0
Order By: Relevance
“…SCAPS-1D has been used to model the perovskite-based solar cells’ device properties. A good agreement between experimental findings and simulation results may be shown using SCAPS-1D. These semiconductor formulas as eqs – include the Poisson equation (eq ), which corresponds the electrostatic potential to the overall charge density, the continuity formula for holes (eq ), and the continuity equation for electrons (eq ), and they are employed to determine solar cell quality attributes. Furthermore, by accounting for Shockle–Read–Hall (SRH) recombination statistics, this software simulates the device’s operation. , …”
Section: Materials and Methodologymentioning
confidence: 99%
“…SCAPS-1D has been used to model the perovskite-based solar cells’ device properties. A good agreement between experimental findings and simulation results may be shown using SCAPS-1D. These semiconductor formulas as eqs – include the Poisson equation (eq ), which corresponds the electrostatic potential to the overall charge density, the continuity formula for holes (eq ), and the continuity equation for electrons (eq ), and they are employed to determine solar cell quality attributes. Furthermore, by accounting for Shockle–Read–Hall (SRH) recombination statistics, this software simulates the device’s operation. , …”
Section: Materials and Methodologymentioning
confidence: 99%
“…Although the PCE of 2.81% reported in ref is slightly lower than the above-mentioned reports, it was found that the addition of potassium iodide (KI) can be beneficial in improving device stability against humidity. All of these inventions brought a breakthrough in the research on Cs 3 Bi 2 I 9 absorber, generating a lot of interest in the theoretical analysis of different configurations of PSCs with the help of the one-dimensional solar cell capacitance simulator (SCAPS-1D) over the past two years. …”
Section: Introductionmentioning
confidence: 99%
“…Some commonly used ETLs for PSCs include TiO 2 , SnO 2 , ZnO, and PCBM, while commonly used HTLs include spiro-OMeTAD, PTAA, and PEDOT:PSS. 32–35 These materials have been extensively studied and optimized due to their compatibility with perovskite materials, high conductivity, and efficient charge transport. However, the choice of the ETL and HTL depends on the specific application and device architecture.…”
Section: Introductionmentioning
confidence: 99%